Optimalna dolžina vizure digitalnega nivelirja Leica geosystems DNA03 - Mazić, Edin (Geodetski vestnik, 2013)
Digital levels significantly simplify field work with regards to automated staff reading, measurement corrections and data storage. However, these instruments are subject to a number of influences whose effects can cause errors in measurements. This especially applies to the negative influence of refraction, which is a serious limiting factor of accuracy in precise levelling. It is still necessary to rectify the effects of refraction via professional analysis of levelling conditions and then choose the best methodology of work. It is particularly important to determine the optimal line-of-sight distance, which yields quality results while keeping greater work productivity. The impact of sight distance of a Leica DNA03 digital levelon the final results of levelling network was investigated and described in this article.
Keywords: coded staff; digital level; digitalni nevelir; kodirana lata; levelling; nivelman; optimal distance of sight line; refraction; refrakcija optimalna dolžina vizure